PENINGKATAN KEMAMPUAN MENYIMAK DALAM MENGEMUKAKAN KEMBALI POKOK-POKOK BERITA MELALUI METODE DISKUSI TEKNIK BUZZ GROUPS SISWA KELAS VIII SMP NEGERI 1 KAHU KABUPATEN BONE - Jumriati Jumriati (Fakultas Keguruan dan Ilmu Penidikan UIM, 2020)
Abstract: Enhancing Listening Ability to Restate News Highlights Through Buzz Group Discussion Method of Class VIII Students of SMP Negeri 1 Kahu Bone Regency. This study aimed to examine the ability to pay attention in restating the headlines through the discussion method of buzz groups of students of class VIII of SMP Negeri 1 kahu Bone Regency. This research was a class action research. Data collection techniques were observation and assignment through restating the main points of news highlights after applying the buzz group discussion technique. Data were analyzed descriptively qualitatively, and the learning outcomes data that were restating the news highlights were analyzed descriptively quantitative. The results showed that the application of the buzz group discussion method on restating the news highlights at the planning, implementation, and outcome stages had increased. This could be seen in the activities of students and teachers in the application of the buzz group technique discussion in the first cycle were still categorized as less active. In cycle II there was a change in the process that showed average in the active category. In the first cycle, the average value of 73.5 and included in the category that experienced an increase in the second cycle with an average value of 84.9 and included in the high category. Based on the results of research, Indonesian language teachers at SMP Negeri 1 Kahu Bone Regency should use maximum learning methods, so that students were more active in the learning process. Indonesian teachers could use the buzz group discussion method in enhancing listening ability to restate news highlights.Keywords: Improvement, Listening News Highlights, Buzz Groups Technique